Once Were Warriors, but how about Maoritanga Now? Novel and Film as a Dialogic Third Space - Martin Renes, Cornelis (Miscelánea: A Journal of English and American Studies, 2012)
Alan Duff’s bestselling novel Once Were Warriors (1990) raised bitter controversies for its harsh depiction of indigenous alienation in the ghettos of New Zealand’s cities. Duff is part Maori and wrote from his own slum experience, and his text shifted responsibility for the Maori predicament and possible solutions partly back to the victims themselves, which met with fierce criticism from indigenous and progressive non-indigenous readership. Under the direction of Lee Tamahori, also of mixed descent, the novel found its way to the screen in 1995 and thus reached a world audience. Given that Duff’s original screenplay was not used for the homonymous film, it should come as no surprise that novel and film tell different stories. While both embed a dysfunctional Maori family within a crippling urban environment, their content and discursive strategies are not quite the same. Applying a Bakhtinian approach to New Zealand’s postcoloniality, this essay investigates up to what point the discursive dialogue between both narratives obeys the requirements of the narrative medium chosen and results in the marketing of different agendas and sites of contestation.